Bronchial hyperresponsiveness to methacholine in patients with primary Sjögren's syndrome. Issue 1 (January 1991) - Gudbjörnsson, B; Hedenström, H; Stålenheim, G; Hällgren, R
Abstract : The prevalence of bronchial hyperresponsiveness (BHR) to methacholine inhalation in a consecutive series of 21 patients with primary Sjögren's syndrome was studied prospectively. Slight to severe BHR was seen in 12/20 (60%) of the patients. Ten of 12 patients with BHR (83%) had a non-productive cough, wheezing, or intermittent breathlessness. Bronchial hyperresponsiveness was more common in patients with extraglandular symptoms (10/14, 71%) than in those with only glandular symptoms (29%). Spirometrically 29% (6/21) of the patients had 'small airways' disease', and all those had BHR. Of 6/21 (29%) who had diffuse interstitial lung disease, two had BHR. Three of the four patients with obstructive lung function were challenged with methacholine and two of them had BHR. Only two patients with BHR had normal spirometry findings. The data showed that respiratory disease--mostly mild or moderate but even severe bronchial hyperresponsiveness--is commonly seen in patients with primary Sjögren's syndrome.